The Influence of Job Description Implementation, Training and Providing Incentives on Employee Performance at PT. Single Paint Factory Djaja Indah Waru-Sidoarjo - Hendri, Hendri; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Based on the observations of researchers, employees at PT. Djaja Indah Single Paint Factory, there are some employees who feel that satisfaction lies in other things, but on the one hand they also don’t get a point of satisfaction from the authority over the industry for their employees and they don’t like and like their work. towards the direction and goals of employees’ desire to work in the PT industry. Single Paint Factory. the method used is survey method, questionnaire technique. With a population of 40 and a sample of 40 while the data is quantitative. With primary data sources using SPSS tools. The results of the T test concluded that the Job Description variable (X1) has influence and significance on employee performance. training variable (X2) has significant influence on employee performance. that the Incentive variable (X3) has significant influence on employee performance. The results of the F test variable Job Description, Training and Incentive simultaneously or jointly affect the performance of employees at PT. Djaja Indah Single Paint Factory.